Bepridil inhibition of sodium current in rat hippocampal CA1 neurons. - Hu Hui-juan; Yang Dong-mei; Dai De-zhi; Wu Cai-hong; Zhou Pei-ai (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of bepridil on sodium current in rat hippocampal neurons. METHODS: All experiments were performed on acutely isolated hippocampal pyramidal neurons by means of whole-cell patch-clamp techniques. Recording media contained ion channel blockers to allow the selective activation of voltage-dependent sodium currents. RESULTS: Bepridil reduced the amplitudes of sodium current in time- and concentration-dependent manners. The half-blocking time was about 10 min in bepridil 10 micromol.L-1, and IC50 was 2.6 (2.3-2.9) micromol.L-1. Bepridil 10 micromol.L-1 shifted the maximal activation of sodium current from -50 mV to -40 mV, and the characteristic voltage of inactivation from -71 mV to -89 mV without changing the slope factor. CONCLUSION: Bepridil blocked voltage-dependent sodium current of hippocampal CA1 neurons and might have therapeutic actions for ischemia-induced brain damage.